2000
DOI: 10.1155/np.2000.261
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Behavioral Recovery from Sensorimotor Cortex Lesions After Pyramidotomy in Adult Rats

Abstract: Unilateral transection of the bulbar pyramid, performed before the ablation of the ipsilateral sensorimotor cortex, has been shown to facilitate the recovery of operantly conditioned reflexes and compensatory processes in rats. Such enhanced behaviorai recovery was absent when only the sensorimotor cortex was ablated. This phenomenon is explained by the switching of motor activity under the control of the cortico-rubrospinal system. Switching of the descending influences is accomplished through the following l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
1
5
1
Order By: Relevance
“…24 Because the corticospinal and rubrospinal axons possess similar branching patterns in the spinal cord, 25 the corticorubrospinal pathway seems to be a backup to the CST to enhance the behavioral recovery after CST lesion. 26 We also found that GAP-43 immunostaining was increased in neurites other than CST axons in the spinal cord after stroke, suggesting a possibility that stroke-induced denervation also enhances axonal plasticity of non-CST pathways and increases the neurite arborization of the spinal neurons. Further studies are warranted to investigate neuronal plasticity in the spinal cord after stroke.…”
Section: Discussionsupporting
confidence: 50%
“…24 Because the corticospinal and rubrospinal axons possess similar branching patterns in the spinal cord, 25 the corticorubrospinal pathway seems to be a backup to the CST to enhance the behavioral recovery after CST lesion. 26 We also found that GAP-43 immunostaining was increased in neurites other than CST axons in the spinal cord after stroke, suggesting a possibility that stroke-induced denervation also enhances axonal plasticity of non-CST pathways and increases the neurite arborization of the spinal neurons. Further studies are warranted to investigate neuronal plasticity in the spinal cord after stroke.…”
Section: Discussionsupporting
confidence: 50%
“…However, the rubrospinal tract participates in the coordination of movements across joints, such as skilled forelimb movements [33], locomotion [34] and motor responses to pain [35], and possesses very similar branching patterns with the CST in the spinal cord [36]. The cortico-rubrospinal pathway appears to be a backup to the CST to enhance the behavioral recovery after CST lesion [37]. We and others have demonstrated that axonal plasticity of the corticorubral tract [38][40] and other spinal descending pathways [41] contribute to functional recovery after stroke in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Third, descending inputs other than the fast corticospinal elements are used 245. Numerous animal studies involving experimental sensorimotor cortex or spinal cord lesions support the hypothesis that motor recovery involves switching of motor activity to the control of brainstem descending pathways such as the cortico‐rubrospinal, the cortico‐reticulospinal, and the cortico‐vestibulospinal systems 15, 48, 72, 191, 192, 250, 274. Propriospinal neurons may also be involved in strategies for functional recovery.…”
Section: Immediate Effects Of Central Lesionmentioning
confidence: 99%